PERANAN KEJAKSAAN TINGGI DALAM PENCEGAHAN TINDAK PIDANA KORUPSI DI KALIMANTAN TIMUR - Hudali Mukti; Ayu Linanda (Yuriska: Jurnal Ilmiah Hukum, 2019)
East Kalimantan cannot be detached from the spotlight of the prevention and eradication of criminal acts of corruption. This is because of the opportunity that exists in East Kalimantan is more wide open. The number of orientation field a more natural resources in East Kalimantan turns out to be a sweet target object for the perpetrators of the corruptor if no supervision and intensive prevention beforehand by the stakeholders concerned. This is where the role of the Prosecutor in East Kalimantan are challenged not only to uphold the law but also embodies the prevention of the occurrence of the crime of corruption that occurs in East Kalimantan. This research aims to find out and assess the efforts of the Prosecutor of East Kalimantan as well as obstacles faced in preventing criminal acts of corruption. In this study using a Purposive Sampling Technique. The technique of data collection is the observation, in-depth interviews and documentation. The data type is the type of primer and under with data analysis is qualitative. Results achieved in this study the existence of the description of the role of the Prosecutor in carrying out efforts in the prevention and eradication of corruption so that created a conducive society, secure, and comfortable away from the criminal acts of corruption.